Practical Method for Evaluating the Performance of a Biometric Algorithm - DJARA, Tahirou; SOBABE, Abdou-Aziz; VIANOU, COKOU ANTOINE (My University, 2018)
This paper presents a modality-independent method of evaluating the performance of an algorithm in biometrics. The operation mode is about developing a JAVA application that offers the user a graphical representation of the evaluation results. This application is interacting with a MySQL database containing the extracted signatures as well as the matching values of the modalities present in the evaluated biometric system. The evaluation system is used to generate the Genuine Matching and Impostor Matching score distribution curves, the False Match Rate and False Non Match Rate curves and the ROC curve. 1000 lines of code were used to develop the application. The method proposed is original and practical. Thus, an application of this method has been made in the case of a contactless fingerprint modality. We plan to improve the developed method by adding the representation of 4 main operating points (EER, WER, Fixed FMR, Fixed FNMR).
Keywords: Biometrics Performance evaluation Biometric algorithm Genuine Matching (GM) Impostor Matching (IM) False Match Rate (FMR) False Non Match Rate (FNMR) Receiver Operating Characteristic (ROC) Modality-independent